A hybrid particle swarm optimization approach and its application to solving portfolio selection problems - Shamshul Bahar, Yaakob, Prof. Madya; Watada, Junzo (Fuji Technology Press, 2011)
Link to publisher's homepage at http://www.fujipress.jp/